Values as a hobby: the transformation and survival of cultural ritual values in the process of desecration - Kūlis, Māris (Latvijas Universitātes Filozofijas un socioloģijas institūts, 2023)
The paper examines how values lose their sacred or protected significance and turn into values as a hobby. Using an excerpt from Arundhati Roy's novel “The God of Small Things”, a trend of transformation of values is outlined, which raises questions about the importance of different values, both sacred and secular, for the representatives of these values. In short, the question is one of the value of values: is their practice (affirmation) meaningful in the basic sense of these values, or is this practice mere imitation as a hobby? The article gives several examples that show the versatility of this topic. The case of Qutb’s Islamism highlights the importance of the distinction between private and public: the exclusion of the Islamic religion from the public sphere would result in the religion and its values losing their prominent role. Opposite direction of change is evident in the social movement woke, in which secular ideas transform into quasi-religious beliefs (resacralization of values). Finally, an explanation of this contemporary cultural picture of values becoming a hobby (in the dynamics of private-public relations) is sought in Andreas Reckwitz’s observation that the “general” is being replaced by a “singular” logic. Since the sacred and general meaning of values is abolished, this is where the shift in how values are understood is most apparent. Because there is no longer a foundation of sacred myth, individual values become a private matter and have no public meaning.
Keywords: values; sacred; protected; hobby; leisure activity; desacralization; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social anthropology/ethnography; Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::Philosophy of religion